Coinfection and Mortality in Pneumonia-Related Acute Respiratory Distress Syndrome Patients with Bronchoalveolar Lavage: A Prospective Observational Study. Issue 5 (May 2017) - Kao, Kuo-Chin; Chiu, Li-Chung; Hung, Chen-Yiu; Chang, Chih-Hao; Yang, Cheng-Ta; Huang, Chung-Chi; Hu, Han-Chung
ABSTRACT: Background: Pneumonia is the leading risk factor of acute respiratory distress syndrome (ARDS). It is increasing studies in patients with pneumonia to reveal that coinfection with viral and bacterial infection can lead to poorer outcomes than no coinfection. This study evaluated the role of coinfection identified through bronchoalveolar lavage (BAL) examination on the outcomes of pneumonia-related ARDS. Methods: We performed a prospective observational study at Chang Gung Memorial Hospital from October 2012 to May 2015. Adult patients were included if they met the Berlin definition of ARDS. The indications for BAL were clinically suspected pneumonia-related ARDS and no definite microbial sample identified from tracheal aspirate or sputum. The presence of microbial pathogens and clinical outcomes were analyzed. Results: Of the 19, 936 patients screened, 902 (4.5%) fulfilled the Berlin definition of ARDS. Of these patients, 255 (22.7%) had pneumonia-related ARDS and were included for analysis. A total of 142 (55.7%) patients were identified to have a microbial pathogen through BAL and were classified into three groups: a virus-only group (n = 41 [28.9%]), no virus group (n = 60 [42.2%]), and coinfection group (n = 41 [28.9%]). ARDS severity did not differ significantly between the groups ( P  = 0.43). The hospital mortality rates were 53.7% in virus-only identified group, 63.3% in no virus identified group, and 80.5% in coinfection identified group. The coinfection group had significantly higher mortality than virus-only group (80.5% vs. 53.7%; P  = 0.01). Conclusion: In patients with pneumonia-related ARDS, the BAL pathogen-positive patients had a trend of higher mortality rate than pathogen-negative patients. Coinfection with a virus and another pathogen was associated with increased hospital mortality in pneumonia-related ARDS patients.